Just the Servant: An Intersectional Critique of Servant Leadership - Liu, Helena (Journal of business ethics, 2019)
Servant leadership offers a compelling ideal of self-sacrificing individuals who put the needs of others before their own and cultivate a culture of growth in their organisations. Although the theory’s attempts to emphasise the moral, emotional and relational dimensions of leadership are laudable, it has primarily assumed a decontextualised view of leadership untouched by power. This article aims to problematise servant leadership by undertaking an intersectional analysis of an Asian cis-male heterosexual senior manager in Australia. Through in-depth interviews with the manager and his staff, the article shows how his attempts to practice servant leadership were informed by intersecting power dynamics of race, gender, sexuality, age and class that subordinated him to white power. The findings demonstrate the ways servant leadership is necessarily embedded in wider power structures that shape who gets to be a “servant leader” and who remains merely a “servant”.